Development of a multifunctional catalyst for a ``relay'' reaction - Ganai, Anal Kumar; Shinde, Pravin; Dhar, Basab B.; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (RSC Advances, 2013)
In the area of catalysis, nanoparticles and enzymes are two of the most important systems. By amalgamating the two, we present here proof of the concept that it is possible to prepare a multifunctional catalyst that can carry out a ``relay'' reaction. The catalyst consists of a surface bound enzyme on a metal(core)-silica(shell) nanoparticle architecture. Here the enzyme catalyzes the 1st reaction and the metal nanoparticles act as a catalyst for the 2nd reaction of the product from the 1st reaction. In particular, we have studied the catalytic activity of glucosidase grafted Au@mSiO(2) on 4-nitrophenyl-beta-glucopyranoside, where glucosidase will catalyse the 1st step to generate 4-nitrophenol, which acts as a substrate for the next reduction step which is catalysed by the Au nanoparticles present inside the mesoporous silica shell.